Hubungan Dukungan Sosial Keluarga dengan Kematangan Karir Siswa SMA di Jayapura - Yudha Dharma Buana; Rika Febriyanti Rahmat; Yunita Karolina (Journal on Education, 2023)
The purpose of this study was to determine the relationship between emotional independence and family social support with the career maturity of high school students in Jayapura. The hypothesis proposed in this study is the relationship between family social support and career maturity of high school students. The subjects of the study were taken using Cluster Random Sampling as many as 100 people. The characteristics of the subjects were 15-18 years old and attended high school in Jayapura. The data collection method in this study used the scale method, namely the family social support scale and the career maturity scale. Data analysis in this study used simple linear regression analysis and multiple linear regression analysis. The results of the study showed: a positive relationship between family social support and career maturity, indicated by a correlation coefficient of R = 0.515 and a determination coefficient of R² = 0.265 (p <0.01).